Regulasi Dana Kampanye Kolektif untuk Pemilu yang Transparan Dana Berkeadilan Perspektif Sistem Proporsional Terbuka - Abd Hannan (University of Muhammadiyah Malang, 2022)
Since the 1998 reform, Indonesia's general election system (PEMILU) has undergone significant changes, from what was originally a representative system to direct elections, from which previously were held separately to now take place simultaneously. However, in the midst of these improvement efforts, it must be admitted that the building of the current election system still leaves problems. One of them is the problem of organizing elections, especially those related to campaign financing regulations. This study is a critical study of the existence of the Indonesian general election, especially with regard to the regulation of election campaign funds. There are two main issues in this study; 1) Collective campaign funds; 2) Elections with an open proportional system. To make this study focused, these two main issues are then elaborated into two major research questions, what is meant by regulation of collective campaign funds based on open proportional elections? What are its strategic roles and functions in an effort to create transparent and fair elections? This study is a qualitative study with library techniques. The entire data of this writing is sourced from secondary data in the form of library data. In general, the findings of this study contain a conceptual-theoretical explanation of the regulation of collective campaign funds based on open proportional elections, a description as well as an in-depth analysis of the problems of regulation of Indonesian election campaign funds, especially after the implementation of the 2019 simultaneous elections.